2005
DOI: 10.1016/j.apcata.2005.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic activity of Ce3+–TiO2 for 2-mercaptobenzothiazole degradation in aqueous suspension for odour control

Abstract: Abstract:A series of cerium ion-doped titanium dioxide (Ce 3+ -TiO 2 ) catalysts with special 4f electron configuration was prepared by a sol-gel process and characterized by Brunauer-EmmettTeller method, X-ray diffraction, X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance spectroscopy (DRS), and also photoluminescence (PL) emission spectroscopy. The photocatalytic activity of Ce 3+ -TiO 2 catalysts was evaluated in the 2-mercaptobenzothiazole (MBT) degradation in aqueous suspension under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(163 citation statements)
references
References 44 publications
7
155
1
Order By: Relevance
“…That might be the reason why the optimal dosage of ceria was 9 at% under UV illumination. Our results are consistent with the results of earlier studies of photoluminescence and photocatalytic in Ce-doped TiO 2 samples [39,41,42], which suggested that the lower photoluminescence might indicate fewer electron-hole recombination and lead to the increase in photocatalytic activity.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…That might be the reason why the optimal dosage of ceria was 9 at% under UV illumination. Our results are consistent with the results of earlier studies of photoluminescence and photocatalytic in Ce-doped TiO 2 samples [39,41,42], which suggested that the lower photoluminescence might indicate fewer electron-hole recombination and lead to the increase in photocatalytic activity.…”
Section: Resultssupporting
confidence: 83%
“…On the basis of our photocatalytic results, it is believed that the difference in photocatalytic activity with doping concentrations not really relates to the surface adsorption ability, but also relates to the influence of doping concentration on structure and the concentration of electron acceptor (Ce 4+ ions) and oxygen vacancies [36]. Li et al [39] based on photoluminescence measurements proved that Ce doping can accelerate the separation efficiency of charge carriers. According to their results the Ce 4f level plays an important role in interfacial charge transfer and elimination of electron-hole recombinations.…”
Section: Resultsmentioning
confidence: 99%
“…These defects, which are primarily surface oxygen vacancies, cause a change in the local electronic and valence arrangement that stabilizes the trivalent oxidation state (III). 11-13 Ceria and nanoceria can be found in several high-end research technologies, such as solid-oxide fuel cells,14 high-temperature oxidation protection materials,15 catalytic materials, 16,17 and more recently, solar cells. 18 Recently, ceria nanoparticles have emerged as a fascinating and lucrative material in biomedical science due to their unique ability to switch oxidation states between III and IV based on environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that Ce 4f plays vital role for CeO 2 in photocatalytic process [33] and they demonstrated that electrons can be more easily injected into 4f band of CeO 2 because the potential of 4f band of CeO 2 is a little more positive than that of the conduction band of TiO 2 . CeO 2 was chosen as the semiconductor in this work has other reason, that is, CeO 2 has excellent electrontransfer mediator ability under visible light [9], which is helpful to further enhance its charge separation ability.…”
Section: Discussion On the Reaction Mechanismmentioning
confidence: 96%